Remembering Eden: the reception history of Genesis 3: 22-24 - Lanfer, Peter Thacher (Oxford University Press, 2012)
Genesis 3: 22-24: the expulsion narrative -- The tree of life -- Wisdom and the expulsion from the garden -- Access to Eden and the hope for immortality -- Eden and the temple